PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur di BEI) - Muchamad Danu Setiyanto Setiyanto; Rahardja Rahardja (Diponegoro Journal of Accounting, 2012)
Agency conflicts that occur and the managers who misused skills can create earnings management that will ultimately lead to poor quality of corporate earnings. It can be seen from the many cases of corporate accounting reporting scandals that occurred in Indonesia. The objective of this study is to test the effect of corporate governance mechanisms on earnings management and its influence on corporate performance. The population in this study is all the companies in the Manufacturing sector registered a positive return on the Indonesia Stock Exchange, with the financial statements from 2008 to 2010. This study is a quantitative study using multiple regression analysis and simple regression, because this study is a replication of a composite type of research. Multiple regression analysis is used to test the effect of corporate governance mechanisms (skills of managers, the proportion of independent board, audit committees, and institutional ownership) of earnings management, while the simple regression is used to test the effect of earnings management on corporate performance. This study used DEA program, which is a program used to analyze the skills of managers through efficiency approach. The results showed that the skills of managers, the proportion of independent board and audit committee have a negative impact on earnings management, while the ownership of the results showed no significant constitutional, in other words had no effect on earnings management. Related to the performance of the company, based on the analysis conducted it could be concluded that the effect of earnings management on the performance of the company, such as a significant negative effect increasing earnings management, the lower the performance of the company.